2022
DOI: 10.17648/acta.scientiae.6826
|View full text |Cite
|
Sign up to set email alerts
|

Compresión del concepto razón a través del modelo de Pirie y Kieren

Abstract: Background: Research in educational mathematics has shown that elementary school students poorly understand the concept of ratio due to the difficulties that emerge from its interpretation as a fraction. Objective: Therefore, based on the Pirie-Kieren theoretical model, we intend to analyse the comprehension process that appears when students solve tasks on ratio. Design: The approach is qualitative, and the research design was a case study. We used the field observation technique. Context and participants: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Nonetheless, students frequently need help understanding and applying these concepts (Wahyuningrum et al, 2017). Furthermore, Peñaloza and Vásquez (2022) found that elementary school students struggle to formalize their comprehension of ratio due to difficulties in applying mathematical strategies correctly when solving tasks. These challenges stem from several factors, including insufficient instructional practices, disparities in students' formal and informal education, overly standard and superficial teaching methods, and the implementation of unsuitable learning models (Ayan et al, 2019;Zuhra et al, 2018;Andinasari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, students frequently need help understanding and applying these concepts (Wahyuningrum et al, 2017). Furthermore, Peñaloza and Vásquez (2022) found that elementary school students struggle to formalize their comprehension of ratio due to difficulties in applying mathematical strategies correctly when solving tasks. These challenges stem from several factors, including insufficient instructional practices, disparities in students' formal and informal education, overly standard and superficial teaching methods, and the implementation of unsuitable learning models (Ayan et al, 2019;Zuhra et al, 2018;Andinasari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Las dificultades en el aprendizaje de las fracciones en la educación básica son de reconocimiento internacional, es señalado como uno de los conceptos que presenta mayor dificultad a los estudiantes de la educación básica (Aguilar et al, 2022;Ávila, 2019;Butto, 2013;Fandiño, 2007;Parra y Carmona, 2021). Estas dificultades están asociados a la escasa comprensión conceptual de los diferentes significados de las fracciones, a la falta de comprensión del sentido de las operaciones y los errores debido a la extrapolación operativa de los números naturales a las fracciones (Arenas, 2018;Butto, 2013;Gabriel et al, 2013;Fandiño, 2009;Fazio y Siegler, 2011). Al respecto, Arenas-Peñaloza y Rodríguez-Vásquez (2021) consideraron que la baja comprensión conceptual de las fracciones es una problemática a atenderse por su importancia en la comprensión de otros conceptos matemáticos; mientras que Martínez et al (2021) señalaron que los estudiantes del nivel básico tienen dificultades para comprender y emplear las fracciones, siendo importante que interpreten las fracciones en forma correcta porque son la base para el aprendizaje de otros constructos.…”
Section: Introductionunclassified
“…Como bases teóricas de la variable aprendizaje de fracciones se consideraron a las teorías sobre la formación de conceptos matemáticos, entre ellos a la Teoría de campos conceptuales de Vergnaud (1990) quien explicó el proceso de conceptualización mediante el término "esquema" a la que definió como el conjunto de conocimientos y acciones para resolver una situación o problema, consideró que la comprensión de un concepto matemático es mediante el establecimiento de una red de conceptos y relaciones vinculados sobre el concepto. Por su parte, Perie y Kieren (como se citó en Arenas, 2018) propusieron ocho niveles para el proceso de comprensión del concepto matemático, que se inicia en la identificación de los saberes previos, luego realizar actividades diversas, representaciones, generalizaciones, la formalización, establecer conexiones, la argumentación y justificación hasta lograr la comprensión completa del concepto matemático. Por otro lado, Duval (2002) consideró el empleo de las representaciones semióticas como condición para el aprendizaje de la matemática, señaló que toda actividad cognitiva implica transformación de representaciones semióticas, y que la comprensión de algún objeto matemático es por la conversión de una representación en otra y por la coordinación de al menos dos representaciones.…”
Section: Introductionunclassified